Age-dependent effects of Spirulina platensis on hepatic protein carbonylation in Wistar rats - Reni Paramita; Tina Rosiani Zaini (Acta Biochimica Indonesiana, 2025)
Background: Oxidative stress tends to rise as age increases, with the liver being notably affected. Changes in liver function are closely linked to oxidative stress, which targets hepatocytic proteins. Free radicals that attack the liver can cause damage to its proteins, which can be measured through carbonyl level. Spirulina platensis, is a blue-green sea algae which grow in sea waters throughout the world and have been consumed as antioxidants. Objective: The objective of this study was to evaluate the effect of Spirulina platensis administration on carbonyl level in the liver tissues of young adult rats with different ages. Methods: Male Wistar rats aged 8 weeks, 14 weeks, and 20 weeks were given 200 mg/kg BW S. platensis extract orally once a day for 29 days until aged 12 weeks, 18 weeks, and 24 weeks. Control group of each age (only given aquadest) Results: The 12-week group given spirulina showed an increase in carbonyl level of 1,215 times compared to the control group. The 18-week group given spirulina showed a reduction in carbonyl level of 0.686 times compared to the control group. The 24-week group given spirulina showed an increase in carbonyl level of 0.924 times compared to the control group. Conclusion: Spirulina platensis administration decreased the carbonyl level in 18-weeks and 24-weeks old rat compared to control group.